SAHNALASHTIRISH FAOLIYATINING TA’LIMDAGI O‘RNI VA AHAMIYATI - Erkaboyeva, F.G‘. (SCIENCE and SOCIETY, 2025)
This article highlights the role and significance of dramatization activities in the educational process. Dramatization serves as an effective tool for developing students' creative thinking, enhancing communication skills, and fostering emotional adaptability. Establishing dramatization centers in preschool educational institutions can support the imagination and personal development of children. This activity contributes to the development of social adaptability, intercultural understanding, and empathy in children, making it a vital aspect of holistic education.
Keywords: dramatization activities; preschool education; role-playing games; creative development; communication skills; intercultural understanding; emotional development; dramatization center; learning through play; interactive education